Persistence And Patience In Reaching Dream Reflected In Ahmad Fuadi's The Land Of Five Towers Novel (2011): A Psychoanalytic Approach - Yusriani, Metrika Arofah, Dr. Phil Dewi Candraningrum, M. Ed, Titis Setyabudi, S. Si, M. Hum (2013)
The problem of this study is "How the major character to reach his dream in Ahmad Fuadi‟s The Land of Five Towers novel. The study analyzes the novel in term of it‟s structural elements and based on the psychoanalytic approach. The writer employs qualitative method. In this method, those are divided in two categories, primary data sources and secondary data. The primary data source is the novel itself. The secondary data sources are the books about psychoanalysis and other sources, which are related to the analysis. The method of data collection is library research and technique of data collection is descriptive analysis. Based on the analysis, the researcher draws two conclusions: first, based on the structural analysis of the novelit is clear that in The Land of Five Towers novel, Ahmad Fuadi delivers message that persistence and patience are needed in everyone‟s life because it is important and can influence someone‟s life to survive in their environment, because someone who has a strength persistence and patience can show who really they are and show their existance. Second, based on the psychoanalytic approach, it shows that persistence and patience can give effect to people‟s mind.